Concepts and semantics of programming languages 2 : modular and object-oriented constructs with Ocaml, Python, C++, Ada and Java - Hardin, Thérèse; Jaume, Mathieu; Pessaux, Francois; Donzeau-Gouge, Véronique (Computer engineering series (London, England), 2021)
This book - composed of two volumes - explores the syntactical constructs of the most common programming languages, and sheds a mathematical light on their semantics, providing also an accurate presentation of the material aspects that interfere with coding. Concepts and Semantics of Programming Languages 2 presents an original semantic model, collectively taking into account all of the constructs and operations of modules and classes: visibility, import, export, delayed definitions, parameterization by types and values, extensions, etc. The model serves for the study of Ada and OCaml modules, as well as C header files. It can be deployed to model object and class features, and is thus used to describe Java, C++, OCaml and Python classes. This book is intended not only for computer science students and teachers but also seasoned programmers, who will find a guide to reading reference manuals and the foundations of program verification.